Incident sexually transmitted infections and their risk factors in an Aboriginal community in Australia: a population based cohort study. Issue 1 (1st February 2001) - Miller, P J; Law, M; Torzillo, P J; Kaldor, J
Abstract : Objective: To identify risk factors for incident sexually transmitted infections (STI) in a remote Aboriginal community in Australia. Design: A population based cohort study. Setting: An Aboriginal community in central Australia. Participants: 1034 Aboriginal people aged 12–40 years, resident in the study region, seen during the period 1 January 1996 to 30 June 1998 for STI diagnosis. Main outcome measures: Incident rate of gonorrhoea, chlamydia, and syphilis per 100 person years. Results: There were 313 episodes of incident gonorrhoea, 240 of incident chlamydial infection, and 17 of incident syphilis. For gonorrhoea, risk factors were age, substance abuse, and previous prevalent chlamydial infection with a rate ratio (RR) of 3.2 in people aged 15–19 years, 1.6 in people who abused alcohol, and 3.2 in women who had sniffed petrol on a regular basis. For chlamydia, risk factors were sex, age, and a previous history of STI with a RR of 2.7 in people aged 15–19 years. Similar factors were associated with an increased risk of syphilis but the associations were not statistically significant. Conclusion: This study identified objective predictors of incident STI which can be used to target interventions and maximise their impact. The results of this study may well have relevance to indigenous communities in other countries that are faced with high levels of STI and substance abuse.